1990
DOI: 10.1021/j100364a009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of molecular orientation in thin Langmuir-Blodgett films by FT-IR transmission and reflection-absorption spectroscopy

Abstract: By a comparison of infrared reflection-absorption (RA) and transmission intensities, a method for the quantitative evaluation of molecular orientation in thin Langmuir-Blodgett (LB) films has been developed. The enhancement factors for the RA to transmission absorption intensities of hypothetical isotropic films were theoretically calculated by using Hansen's optical formulas for thin multilayer films. By combination of these values with the experimentally determined intensity ratios of the RA to transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
252
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(264 citation statements)
references
References 3 publications
(3 reference statements)
9
252
1
2
Order By: Relevance
“…The LB film thickness was five monolayers. The observed peaks are assigned to asymmetric CH3 stretching (2957.7 cm -1), asymmetric CH2 stretching (2917.3cm-1), symmetric CH3 stretching (2872.4cm-1), symmetric CH2 stretching (2850.0 cm-~ ), asymmetric COO-stretching (1512.8cm-1), and symmetric COOstretching (1446.2 cm -1) modes (Umemura, Kamata, Kawai & Takenaka, 1990). The improved performance of BML…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The LB film thickness was five monolayers. The observed peaks are assigned to asymmetric CH3 stretching (2957.7 cm -1), asymmetric CH2 stretching (2917.3cm-1), symmetric CH3 stretching (2872.4cm-1), symmetric CH2 stretching (2850.0 cm-~ ), asymmetric COO-stretching (1512.8cm-1), and symmetric COOstretching (1446.2 cm -1) modes (Umemura, Kamata, Kawai & Takenaka, 1990). The improved performance of BML…”
Section: Resultsmentioning
confidence: 92%
“…LB films were deposited on the surface of an SiO2 BML substrate and an n-type Si(100) substrate of resistivity larger than 1 f~ cm, without removing the surface native oxide, by a conventional method using a solution of stearic acid in benzene spread on the surface of purified water containing 5 x 10 -4 M BaCI2. By comparing the transmission spectra of LB films deposited on the Si(100) substrate and the IRAS spectrum of the BML substrate, it is concluded that LB films are deposited with their hydrocarbon chain axis almost perpendicular to the substrate surface (Umemura, Kamata, Kawai & Takenaka, 1990). The spectra with the LB films were measured by using a Fourier-transformed infrared (FFIR) spectrometer (Perkin-Elmer model 1600) and a TGS detector (4cm -1 resolution and 100 scans).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the signal enhancement effect, this orientation of the optical electric field is another advantage of the RAS method, because it can be quite helpful in evaluating the molecular orientation in the organized molecular films such as LB films. That is, comparison of the absorption spectra observed with the RAS and transmission method, in the latter of which the optical electric field is parallel to the substrate surface (with the s-polarization) or oblique (with the p-polarization), provides information about the orientation of the transition dipole moments [3]. However, this comparison may be useless if the structure of the films deposited on the substrates for the RAS and transmission methods are largely different.…”
Section: Molecular Orientationmentioning
confidence: 99%
“…For example, mono-and multilayered Langmuir-Blodgett (LB) films of cadmium octadecanate were intensively studied by this method with silver substrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brewster-angle microscopy (BAM) images a monolayer by measuring the refractive index difference between water and organic molecules at the surface [9]. Infrared reflection absorption spectroscopy (IRRAS) is able to detect vibrational modes of molecules at the surface monolayer [10]. But BAM gives only information of overall refractive index Different Adsorption Behavior of Rare Earth and Metallic Ion Complexes on … -Woongmo Sung et al change at the surface thus is not suitable to monitor the structure of a Langmuir monolayer and the interfacial water separately.…”
Section: Introductionmentioning
confidence: 99%